The Monastic Diet in the Light of Medical Science. Theodoret of Cyrus and Medics on Dates and Figs - Kokoszko, Maciej; Jagusiak, Krzysztof; Dybała, Jolanta (Studia Ceranea, 2020)
The aim of this article is to present the menu of early Christian monks in the context of the findings of Greek and Roman medicine in the field of dietetics. It draws from the passages of Historia religiosa by Theodoret of Cyrus about the consumption of dates and figs by Syrian ascetics. Both species of fruit did not comprise the basis of the monks’ limited diet. Figs and dates were treated as additional food by them, which they ate rarely and in small quantities. According to Theodoret, they did so especially when their bodies were weakened, during long and exhausting fasts. According to modern dietetics, this was justified as both figs and dates are calorie- and nutrientrich foods, which consumed even in small amounts can significantly supplement an adult’s daily balance in this regard. The authors of ancient and medical texts stemming from the tradition of Antiquity (Galen, Oribasius, Antimus, Aëtius of Amida, Paul of Aegina and others) also drew attention to the nutritious quality of dates and figs, in addition to numerous others health-promoting properties (especially in the context of the latter species). However, they further noted that excessive consumption of both fruits could lead to some health problems. In the context of these findings, occasional consumption of dates and figs by Syrian ascetics appears justified, as they could provide their weakened bodies with food of high energy value and nutritious content, whose small amount – and, therefore, fitting in the ideal of mortification – would suffice to improve their health condition.